Evaluation of Ambient Air Quality Monitoring System in Jakarta: A Literatur Review - Michelle Gunawan; Riri Asyahira; Filson M Sidjabat (Fakultas Teknik, 2020)
As the first step to air pollution control and public health protection, Air quality monitoring systems provides information that indicate the extend of pollution in an area, the source of pollution and the types of pollutants. Therefore, the aim of this study is to evaluate Jakarta’s air quality monitoring system by comparing it to the US, which participates in Indonesia’s air quality monitoring system by using their own system. In specific, parameters such as air quality index, monitoring stations, regulation and data availability are to be compared through reviewing various literatures in detail. The result obtained shows that the monitoring station amount is already ideal and complies to the U.S regulation. Indonesia’s ambient air quality standard need to be stricter and Air Pollutant Standard Index should include PM2.5 as a parameter obtains significantly better results. Air quality data is available and accessible, although it needs to be integrated and provide real time information in a simple and effective way.